Food as a factor controlling the breeding of Puffinus lherminieri. - Harris, M. P. (1969)
BIB Now: 3597
English
96
Keywords: PR, EC -- Food as a factor controlling the breeding of Puffinus lherminieri. -- birds, bird population, feeding, Audubon's shearwater -- aves, piqueros, alimento, pufino